Universal Visual Features Might Be Necessary for Fluent Reading. A Longitudinal Study of Visual Reading in Braille and Cyrillic Alphabets - Bola, Łukasz; Radziun, Dominika; Siuda-Krzywicka, Katarzyna; Sowa, Joanna E.; Paplińska, Małgorzata; Sumera, Ewa; Szwed, Marcin (Frontiers in Psychology, 2017)
It has been hypothesized that efficient reading is possible because all reading scripts have been matched, through cultural evolution, to the natural capabilities of the visual cortex. This matching has resulted in all scripts being made of line-junctions, such as T, X or L. Our aim was to test a critical prediction of this hypothesis: visual reading in an atypical script that is devoid of line-junctions (such as the Braille alphabet read visually) should be much less efficient than reading in a “normal” script (e.g., Cyrillic). Using a lexical decision task, we examined Visual Braille reading speed and efficiency in sighted Braille teachers. As a control, we tested learners of a natural visual script, Cyrillic. Both groups participated in a two semester course of either visual Braille or Russian while their reading speed and accuracy was tested at regular intervals. The results show that visual Braille reading is slow, prone to errors and highly serial, even in Braille readers with years of prior reading experience. Although subjects showed some improvements in their visual Braille reading accuracy and speed following the course, the effect of word length on reading speed (typically observed in beginning readers) was remained very sizeable through all testing sessions. These results are in stark contrast to Cyrillic, a natural script, where only three months of learning were sufficient to achieve relative proficiency. Taken together, these results suggest that visual features such as line junctions and their combinations might be necessary for efficient reading.